2010
DOI: 10.1007/s11307-010-0426-6
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence Base of FDG-PET/CT Imaging in the Clinical Management of Malignant Pleural Mesothelioma: Emerging Significance of Image Segmentation and Global Disease Assessment

Abstract: Increasingly, integrated positron emission tomography-computed tomography (PET/CT) imaging is playing a crucial role in the assessment of patients with known or suspected malignant pleural mesothelioma (MPM). Based on the data reported in the literature, this combined modality is likely to become the instrument of choice for examining patients of MPM. The research on this subject has focused on the following five domains: (1) differentiation of MPM from other benign pleural diseases, (2) preoperative staging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 50 publications
(59 reference statements)
0
35
0
2
Order By: Relevance
“…Its usefulness was first documented in lung cancer, but it is now also one of the imaging tools for pleural diseases [4,5,6,7]. However, a major drawback with FDG-PET is that any kind of inflammation can produce high uptake values in almost any tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Its usefulness was first documented in lung cancer, but it is now also one of the imaging tools for pleural diseases [4,5,6,7]. However, a major drawback with FDG-PET is that any kind of inflammation can produce high uptake values in almost any tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies performed in patients with a variety of different neoplastic diseases-such as head and neck cancer (7,8), lung cancer (9,10), pleural mesothelioma (11), pharyngeal cancer (12), thyroid cancer (13), non-Hodgkin lymphoma (14,15), osteosarcoma (16,17), and soft-tissue sarcoma (18)-showed that 18 F-FDG PET/CT, by determining the uptake and volume of metabolic active lesions in the whole body, allows direct measurement of metabolic tumor burden. In MM, therefore, metabolic tumor burden measured by 18 F-FDG PET/CT may reflect plasma cell mass throughout the bone marrow in the whole body, thus providing a novel potential prognostic factor.…”
mentioning
confidence: 99%
“…There is an urgent need for a standard widely adopted method to deal with partial volume effects, because this will accelerate the high potential of quantitative PET in oncology. Attempts are being made by both the industry and academia to develop robust partial volume correction methods that can be easily implemented in clinical practice [11,12].…”
mentioning
confidence: 99%